Comparison of two alternatives of combined drying to process blueberries (O'Neal): Evaluation of the final quality. Issue 8 (10th June 2016) - Rodriguez, A.; Zaro, M. J.; Lemoine, M. L.; Mascheroni, R. H.
ABSTRACT: In this work, we examined and compared two combined alternatives for the drying of blueberries (O'Neal). Pretreatments of osmotic dehydration (60°Brix sucrose solution at 40°C for 6 h) and hot air drying (HAD) (60°C, 2.5 m/s for 90 min) were performed to reach the same water content. Pretreated blueberries were then dried by microwave at different microwave output power values: 562.5, 622.5, and 750 W. The combined drying processes were also compared with HAD alone (control). The effects of the processes over blueberries were studied in terms of decrease in water content, drying rate (DR), mechanical properties (firmness and stiffness), optical properties ( L *, a *, and hue angle ( h )), antioxidant capacity, and rehydration capacity. The hot air–microwave drying decreased the process time and presented a high drying rate compared with the osmotic dehydration–microwave processes and the control drying. In terms of quality, the antioxidant and rehydration capacities were the most affected. The results showed that the best drying method to obtain the desired final product was the hot air–microwave drying (750 W).